Spatial and temporal variation and distribution of mesozooplankton in the Drake Passage sampled with the continuous Plankton Recorder. (February 2023) - Esquivel-Garrote, Octavio; Muxagata, Erik; Hosie, Graham W.
Abstract: Zooplankton is the main link between primary producers and higher trophic levels in marine foods webs. In the Southern Ocean, zooplankton could be key in identifying environmental changes, given rapid warming registered in the area in the last decades. The Drake Passage is a choke point of oceanographic processes, since it is the narrowest and most dynamic path of the Antarctic Circumpolar Current (ACC). The objective of this study was to determine the horizontal spatial variations of mesozooplankton in the Drake Passage relative to Southern Ocean oceanographic fronts and zones. Three transects were sampled using a CPR in the Drake Passage during the austral summer of 2009 and 2010. Temperature and salinity were measured at 1-min intervals with a thermosalinograph and Chlorophyll a data extracted from NASA's ocean color web. Organisms were counted and identified to the lowest level, resulting in 53 taxa, with 24 identified to species, eight to genus and 21 to a higher taxonomic level. Four fronts (Subantarctic Front - SAF, Polar Front - PF, South of ACC Front - SACCF and Peninsula Front -PF*) delimiting five zones (Subantarctic Zone - SAZ, Polar Front Zone - PFZ, Antarctic Zone - AZ, Southern Zone - SZ and Transitional Water Zone with Bellingshausen Sea Influence TBW) were registered according to temperature values. Higher mesozooplankton abundances were recorded in the PFZ (412.0 ± 27.9 ind. m −3 ) in 2009 and in the AZ (128 ± 12.3 ind. m −3 ) during 2010. Copepoda were the most abundant group (82%), followed by crustacean eggs (4.3%) and Larvacea (4.0%). Within Copepoda, the most abundant taxa were Calanidae copepodites (33.5 ± 53.4 ind. m −3 ), Oithona spp. (25.4 ± 27.1 ind. m −3 ) and Calanus simillimus (19.4 ± 26.1 ind. m −3 ). Differences in community structure were found between zones with C. simillimus and Thysanoessa macrura contributing most to the dissimilarities between the SAZ and the PFZ, Ctenocalanus citer between the PFZ and AZ, Euphausia superba between zones south of the Polar Front and Salpa thompsoni between the SZ and TBW. Some species or taxa are related to or: indicators of a particular zone. The PFZ was the most diverse and had higher mesozooplankton abundances compared to the other zones. Changes in composition are perceptible compared to previous studies, with a decrease of larger organisms and richness, lack of larger copepods, decrease of krill and increase of S. thompsoni abundances. Highlights: Fronts and zones of the ACC delimit mesozooplankton communities in the Drake Passage. Changes in the community composition are perceptible from 80 years to the present. Salps are increasing their distribution range, reaching southward from SAZ to SZ. The Polar Front does not act as biogeographic boundary in this zone. We found key species as indicators of particular zones.